![image](https://tex.z-dn.net/?f=3%2B2log_%7Bx%2B1%7D3%3D2log_3%28x%2B1%29%5C%5C%0A2%28log_3%28x%2B1%29-%5Cfrac%7B1%7D%7Blog_3%28x%2B1%29%7D%29-3%3D0%5C%5C%0A%28t%3Dlog_3%28x%2B1%29%29%5C%5C%0A2%28t-1%2Ft%29-3%3D0%5C%5C%0A+%5Cfrac%7B2t%5E2-3t-2%7D%7Bt%7D+%3D0%3D%3E%5C%5C%0At%5Cneq0%3B%5C%5C%0A2t%5E2-3t-2%3D0%5C%5Ct%3D+%5Cfrac%7B3%5E%2B_-%5Csqrt%7B9%2B16%7D%7D%7B4%7D+%3D%5Cfrac%7B3%5E%2B_-5%7D%7B4%7D%5C%5C%0At%3D2%3D%3Elog_3%28x%2B1%29%3D2%3B%5C%5Cx%2B1%3D3%5E2%3B%5C%5Cx%3D8%5C%5C%5C%5Ct%3D-1%2F2%3D%3Elog_3%28x%2B1%29%3D-1%2F2%3B%5C%5Cx%2B1%3D+%5Cfrac%7B1%7D%7B%5Csqrt3%7D+%3B%5C%5Cx%3D%5Cfrac%7B1%7D%7B%5Csqrt3%7D-1)
\\
t\neq0;\\
2t^2-3t-2=0\\t= \frac{3^+_-\sqrt{9+16}}{4} =\frac{3^+_-5}{4}\\
t=2=>log_3(x+1)=2;\\x+1=3^2;\\x=8\\\\t=-1/2=>log_3(x+1)=-1/2;\\x+1= \frac{1}{\sqrt3} ;\\x=\frac{1}{\sqrt3}-1" alt="3+2log_{x+1}3=2log_3(x+1)\\
2(log_3(x+1)-\frac{1}{log_3(x+1)})-3=0\\
(t=log_3(x+1))\\
2(t-1/t)-3=0\\
\frac{2t^2-3t-2}{t} =0=>\\
t\neq0;\\
2t^2-3t-2=0\\t= \frac{3^+_-\sqrt{9+16}}{4} =\frac{3^+_-5}{4}\\
t=2=>log_3(x+1)=2;\\x+1=3^2;\\x=8\\\\t=-1/2=>log_3(x+1)=-1/2;\\x+1= \frac{1}{\sqrt3} ;\\x=\frac{1}{\sqrt3}-1" align="absmiddle" class="latex-formula">